Molecular Epidemiological Survey of Hemoglobinopathies in the Wuxi Region of Jiangsu Province, Eastern China. (October 2013) - Lin, Min; Han, Zhi-Jun; Wang, Qian; Zheng, Lei; Wang, Yan; Yang, Hui; Huang, Yue; Lin, Fen; Zhan, Xiao-Fen; Lin, Chun-Ping; Wu, Jiao-Ren; Luo, Zhao-Yun; et al.
<x xml:space="preserve">Abstract</x> In order to determine the prevalence and molecular characterization of hemoglobinopathies in the Wuxi region of Jiangsu Province in the People's Republic of China (PRC), a total of 10, 297 healthy people selected from a regional hospital were screened. Hemoglobin (Hb) electrophoresis, complete blood cell (CBC) count, polymerase chain reaction (PCR), DNA sequencing, reverse dot-blot and multiplex ligation-dependent probe amplification (MLPA) were used to detect Hb variants, thalassemias and hereditary persistence of fetal Hb (HPFH). Two thousand and twenty-one adult subjects were screened for thalassemia, five cases were identified as α-thalassemia (α-thal) carriers including three cases of the –α3.7 (rightward) deletion, one case of the – –SEA deletion and one case of β-thal [IVS-II-654 (C>T), (HBB: c.316-197C>T)]. The incidence of Hb variants, thalassemia and HPFH/δβ-thal were 0.136% (14/10, 297), 0.25% (5/2021) and 0.0001% (1/10, 297), respectively. Eight genotypes of Hb variants were found, including Hb E [β26(B8)Glu→Lys, GAG>AAG; HBB: c.79G>A], Hb J-Bangkok [β56(D7)Gly→Asp (GGC>GAC); HBB; c.170G>A], Hb G-Coushatta [β22(4)Glu→Ala (GAA>GCA); HBB: c.68A>C], Hb Queens [α34(B15)Leu→Arg (CTG>CGG) (α2 or α1); HBA2: c.104T>G (or HBA1)], Hb I [α16(A14)Lys→Glu, AAG>GAG (α1); HBA1: c.49A>G], Hb Beijing [α16(A14)Lys→Asn (AAG>AAC or AAT) (α2 or α1); HBA2: c.51G>C (or HBA1) or 51G>T (or HBA1)], Hb Ube-2 [α68(E17)Asn→Asp (AAC>GAC) (α2 or α1); HBA2: c.205A>G (or HBA1)] and Hb G-Taipei [β22(B4)Glu→Gly (GAA>GGA); HBB: c.68A>G]. A Sicilian δβ0-thal, identified for the first time in Asia, was also found in this survey.